Shared decision making and medication adherence in patients with COPD and/or asthma: the ANANAS study - Achterbosch, Maria; Vart, Priya; van Dijk, Liset; van Boven, Job F. M. (Frontiers in Pharmacology, 2023)
Background: Medication adherence to inhalation medication is suboptimal in patients with COPD and asthma. Shared decision making (SDM) is proposed as an intervention to improve medication adherence. Despite its wide promotion, evidence of SDM's association with greater medication adherence is scarce. Also, it is unknown to what degree patients presently experience SDM and how it is associated with medication adherence.Objective: To (i) assess the level of SDM and (ii) medication adherence, (iii) explore the relation between SDM and medication adherence and (iv) investigate possible underlying mechanisms.Methods: Cross-sectional observational study.A survey was distributed among Dutch patients with COPD and/or asthma using inhaled medication.Medication adherence was measured using the Test of Adherence to Inhalers (TAI-10), and SDM by the 9-item Shared Decision-Making questionnaire (SMD-Q-9). Feeling of competence, relatedness and feeling of autonomy from the Self-Determination Theory (SDT) were considered as possible mechanisms. The primary outcome was adherence.Results: A total of 396 patients with complete information on relevant covariates were included.Mean SDM-Q-9 score was 26.7 (SD 12.1, range 0-45) and complete adherence was 41.2%. The odds ratio for the association of SDM with adherence was 1.01 (95% CI: 0.99, 1.02). This only changed minimally when adjusted for mediators (mediating effect <3%).The patient experienced level of SDM in daily practice and medication adherence have room for improvement. No association between SDM and medication adherence was observed.